A conceptual study of high speed rotorcraft - Tanabe, Y.; Aoyama, T.; Kobiki, N.; Sugiura, M.; Miyashita, R.; Sunada, S.; Kawachi, K.; Nagao, M. (My University, 2014)
A study group of future rotorcraft is formed in JAXA with participants from a wide spectra of organizations in Japan. Taking the helicopter market in Japan as a study case, four potential high speed rotorcraft (VTOL aircraft) missions are discussed. When a capability of hovering is required, compound helicopter is concluded as the most suitable design configuration. A simplified conceptual design process for a compound helicopter is described where a wing and propellers are added to a single rotor helicopter. A compound helicopter concept for high speed EMS (Emergency Medical Service) is proposed. The result of the conceptual design is compared with a conventional helicopter and the cost expense is illustrated. If also considering the cost to maintain a base hospital, a high speed rotorcraft with significant higher cost is acceptable which covers a much wider area providing effective first aid to critical patients